2015
DOI: 10.1099/jgv.0.000305
|View full text |Cite
|
Sign up to set email alerts
|

Stability of murine scrapie strain 87V after passage in sheep and comparison with the CH1641 ovine strain

Abstract: Breed-and prion protein (PRNP) genotype-related disease phenotype variability has been observed in sheep infected with the 87V murine scrapie strain. Therefore, the stability of this strain was tested by inoculating sheep-derived 87V brain material back into VM mice. As some sheep-adapted 87V disease phenotypes were reminiscent of CH1641 scrapie, transgenic mice (Tg338) expressing ovine prion protein (PrP) were inoculated with the same sheep-derived 87V sources and with CH1641. Although at first passage in VM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…In any case, it is of interest that the combined propagation of a single isolate on low and high expresser mice recapitulated part of the natural scrapie strains variation as documented by transmission to high expresser mice9. In particular, LA19K and the reference scrapie strain CH1641 exhibit identical features44. Thus panels of transgenic mice harbouring various PrP C levels might represent a relevant tool in an attempt to learn more about the determinism underlying the diversity and evolution of natural prions.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, it is of interest that the combined propagation of a single isolate on low and high expresser mice recapitulated part of the natural scrapie strains variation as documented by transmission to high expresser mice9. In particular, LA19K and the reference scrapie strain CH1641 exhibit identical features44. Thus panels of transgenic mice harbouring various PrP C levels might represent a relevant tool in an attempt to learn more about the determinism underlying the diversity and evolution of natural prions.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of tg-shVRQ mice, a recent seminal paper showed that the overexpression of PrP determines the selection of the 19 K strain component in these mice 46 . Furthermore, the 19 K scrapie-derived strain showed strain features indistinguishable from CH1641 in tg-shVRQ 46,50 . Finally, experimental transmission per se could have favoured the propagation of the 19 K component, as it has been shown that experimental challenge of sheep with classical scrapie can lead to the emergence of a 19 K CH1641-like component, which was hidden in the homotypic inoculum 51 .…”
Section: Species Linementioning
confidence: 96%
“…Importantly, both murine lines were able to propagate this conformer. The phenotype associated to this form of the agent resembled that of CH1641-like isolates 46,47,59,60 . CH1641 scrapie is associated with a PrP res banding pattern with low (19-20 kDa) NG species and possesses distinctive biological properties.…”
Section: Discussionmentioning
confidence: 88%